2005
DOI: 10.1212/01.wnl.0000171704.50395.ba
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic markers of recanalization in patients with ischemic stroke treated with rt-PA

Abstract: Baseline levels of alpha2-antiplasmin were predictive of recanalization but were not related to the long-term outcome in patients treated with rt-PA within the first 3 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 32 publications
3
44
0
5
Order By: Relevance
“…15, 16, 30 The present findings are also consistent with recent reports that increased levels of a2AP may contribute to the failure of TPA treatment in humans and in mice. 13, 14 …”
Section: Discussionmentioning
confidence: 99%
“…15, 16, 30 The present findings are also consistent with recent reports that increased levels of a2AP may contribute to the failure of TPA treatment in humans and in mice. 13, 14 …”
Section: Discussionmentioning
confidence: 99%
“…5 After an ischemic stroke, the likelihood of recanalization depends in large measure on the composition and size of the clot and on the time from onset to treatment. In addition, it seems reasonable to hypothesize that the baseline level of fibrinolytic inhibitors correlates inversely with the probability of recanalization, 6,7 although no studies have reported the importance of the time sequence of changes of fibrinolysis inhibitors. Moreover, the failure of thrombolysis in ischemic heart disease has been associated with an insufficient reduction in the levels of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of PAI-1 <34 ng/ml predict poor response to thrombolysis. A second study of 63 ischemic stroke found that recanalization with IV-tPA was predicted by lower levels of α2-antiplasmin and fTAFI (functional thrombin activated fibrionolysis inihibitor) [87]. A level of α2-antiplasmin >85% predicted recanalization with a sensitivity of 25% and specificity of 85%.…”
Section: Biomarkers Of Arterial Recanalizationmentioning
confidence: 99%